2011
DOI: 10.1073/pnas.1100930108
|View full text |Cite
|
Sign up to set email alerts
|

Functional motor recovery from brain ischemic insult by carbon nanotube-mediated siRNA silencing

Abstract: Stroke is the second cause of death worldwide with ischemic stroke accounting for 80% of all stroke insults. Caspase-3 activation contributes to brain tissue loss and downstream biochemical events that lead to programmed cell death after traumatic brain injury. Alleviation of symptoms following ischemic neuronal injury can be potentially achieved by either genetic disruption or pharmacological inhibition of caspases. Here, we studied whether silencing of Caspase-3 using carbon nanotube-mediated in vivo RNA int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
125
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 218 publications
(128 citation statements)
references
References 44 publications
3
125
0
Order By: Relevance
“…Results obtained in this study demonstrated lack of toxicity of fMWNTs and their efficiency as cytosolic siRNA carriers in addition to the bioactivity of the delivered siRNA as demonstrated by efficient gene silencing in vivo superseding the efficiency of cationic liposomal vectors as previously reported in other studies using stroke and cancer disease models. 15,22 Interestingly, amino functional groups on the MWNTNH 3 + sidewalls can be further modified such as building dendritic structures as reported previously. 26,27 Engineering the degree and type of dendritic branching is expected to affect the degree of siRNA association and gene silencing efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results obtained in this study demonstrated lack of toxicity of fMWNTs and their efficiency as cytosolic siRNA carriers in addition to the bioactivity of the delivered siRNA as demonstrated by efficient gene silencing in vivo superseding the efficiency of cationic liposomal vectors as previously reported in other studies using stroke and cancer disease models. 15,22 Interestingly, amino functional groups on the MWNTNH 3 + sidewalls can be further modified such as building dendritic structures as reported previously. 26,27 Engineering the degree and type of dendritic branching is expected to affect the degree of siRNA association and gene silencing efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Functional recovery was achieved to perilesional levels after stereotactic administration of the therapy in both pre and postlesioned animals. 15 Overall, although fCNTmediated gene silencing is at an early preclinical stage, recent studies have shown that f-CNT offer significant benefits in the area of gene therapy and more specifically gene silencing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 This type of nanotubes has been extensively used for different applications including therapy and imaging. [32][33][34] In particular, they have been explored as carriers of small interference RNA for gene silencing. 32,33 1 Their biodistribution and biodegradation have been also thoroughly assessed.…”
mentioning
confidence: 99%
“…[32][33][34] In particular, they have been explored as carriers of small interference RNA for gene silencing. 32,33 1 Their biodistribution and biodegradation have been also thoroughly assessed. 5,35 In this context, we recently studied the kinetics of degradation of MWCNTs with different types of functionalization into long-term cultures of microglia using Raman spectroscopy.…”
mentioning
confidence: 99%